2017
DOI: 10.3390/ijerph14101157
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Transfer of Pyrethroid Residues from Herbal Teas to Infusion and Influence of Physicochemical Properties of Pesticides

Abstract: The transfer of pesticide residues from herbal teas to their infusion is a subject of particular interest. In this study, a multi-residue analytical method for the determination of pyrethroids (fenpropathrin, beta-cypermethrin, lambda-cyhalothrin, and fenvalerate) in honeysuckle, chrysanthemum, wolfberry, and licorice and their infusion samples was validated. The transfer of pyrethroid residues from tea to infusion was investigated at different water temperatures, tea/water ratios, and infusion intervals/times… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 31 publications
(40 reference statements)
0
7
0
Order By: Relevance
“…The commonly used temperature in infused teas is between 85ºC and 100ºC that was used in our previous study which obtained good results (Kelebek, 2016). In addition, the conditions obtained from the extant literature are also in a similar temperature range (Ariffin, Heong Chew, Bhupinder, Karim, & Huda, 2011;Gan & Ting, 2017;Pan et al, 2018;Xiao et al, 2017). One gram of elderberry flower was weighed and decanted into a 250 ml beaker and 200 ml of water was added and then brewed at 85°C for 5 and 30 min.…”
Section: Preparation Of Elderberry Extractsmentioning
confidence: 72%
“…The commonly used temperature in infused teas is between 85ºC and 100ºC that was used in our previous study which obtained good results (Kelebek, 2016). In addition, the conditions obtained from the extant literature are also in a similar temperature range (Ariffin, Heong Chew, Bhupinder, Karim, & Huda, 2011;Gan & Ting, 2017;Pan et al, 2018;Xiao et al, 2017). One gram of elderberry flower was weighed and decanted into a 250 ml beaker and 200 ml of water was added and then brewed at 85°C for 5 and 30 min.…”
Section: Preparation Of Elderberry Extractsmentioning
confidence: 72%
“…In an investigation conducted by Pitoi et al [35] , the concentrations of lambda-cyhalothrin, cypermethrin, fenvalerate, and deltamethrin in dried tea leaves were detected in their studies and were all below the MRLs, which is in agreement with the current study. In another similar study in China, specifically on tea marketed in the Tehran market, their results revealed that consumed tea in Iran is free of pesticide residues or has residues that are lower than existing MRLs [4] , [45] . Natural factors such as temperature, rainfall, volatilization, photolysis, ventilation, biodegradation, pH, dew, and growth dilution, as well as the pre-harvest period between the last application and harvesting, can cause pesticide residues in tea bushes to degrade [39] , [32] , [44] , [40] .…”
Section: Resultsmentioning
confidence: 97%
“…The brewing factor is the transfer rate of pesticides from made tea into tea infusion, which is the ratio of the residues in tea infusion to that in made tea. The brewing factor is highly related to the water solubility (Ws) of pesticides . Neonicotinoid pesticides have a relative high water solubility, with a brewing factor of tea infusion as high as 40–81.6% .…”
Section: Methodsmentioning
confidence: 99%